Quality of life measurement in alopecia areata. Position statement of the European Academy of Dermatology and Venereology Task Force on Quality of Life and Patient Oriented Outcomes. (9th June 2021) - Chernyshov, P.V.; Tomas‐Aragones, L.; Finlay, A.Y.; Manolache, L.; Marron, S.E.; Sampogna, F.; Spillekom‐van Koulil, S.; Pustisek, N.; Suru, A.; Evers, A.W.M.; Salavastru, C.; Svensson, A.; et al.
Abstract: New treatment options may lead to an increased interest in using reliable and sensitive instruments to assess health‐related quality of life in people with alopecia areata (AA). The purpose of this paper is to present current knowledge about quality of life assessment in AA. The dermatology‐specific Dermatology Life Quality Index (DLQI) was the most widely reported health‐related quality of life instrument used in AA. Three AA‐specific (Alopecia Areata Symptom Impact Scale, Alopecia Areata Quality of Life Index and Alopecia Areata Patients' Quality of Life) and three hair disease‐specific instruments (Hairdex, Scalpdex and 'hair‐specific Skindex‐29') were identified with a range of content and validation characteristics: there is little evidence yet of the actual use of these measures in AA. Scalpdex is the best‐validated hair disease‐specific instrument. Further extensive validation is needed for all of the AA‐specific instruments. The European Academy of Dermatology and Venereology Task Force on Quality of Life and Patient Oriented Outcomes recommends the use of the dermatology‐specific DLQI questionnaire, hair disease‐specific Scalpdex and the alopecia areata‐specific instruments the Alopecia Areata Symptom Impact Scale or Alopecia Areata Quality of Life Index, despite the limited experience of their use. We hope that new treatment methods will be able to improve both clinical signs and health‐related quality of life in patients with AA. In order to assess the outcomes of trials on these new treatment methods, it would be helpful when further development and validation of AA‐specific instruments is being encouraged and also conducted.